Essential oils and plant extracts for tropical fruits protection: from farm to table - Mohd Israfi, Nur Aisyah; Mohd Ali, Muhamad Israq Amir; Manickam, Sivakumar; Sun, Xun; Goh, Bey Hing; Tang, Siah Ying; Ismail, Norsharina; Abdull Razis, Ahmad Faizal; Ch’ng, Soo Ee; Chan, Kim Wei (Frontiers Research Foundation, 2022)
The tropical fruit industry in Malaysia makes up a large proportion of the agriculture sector, contributing to the local economy. Due to their high sugar and water content, tropical fruits are prone to pathogenic infections, providing optimal microorganism growth conditions. As one of the largest exporters of these fruits globally, following other Southeast Asian countries such as Thailand, Indonesia and the Philippines, the quality control of exported goods is of great interest to farmers and entrepreneurs. Traditional methods of managing diseases in fruits depend on chemical pesticides, which have attracted much negative perception due to their questionable safety. Therefore, the use of natural products as organic pesticides has been considered a generally safer alternative. The extracts of aromatic plants, known as essential oils or plant extracts, have garnered much interest, especially in Asian regions, due to their historical use in traditional medicine. In addition, the presence of antimicrobial compounds further advocates the assessment of these extracts for use in crop disease prevention and control. Herein, we reviewed the current developments and understanding of the use of essential oils and plant extracts in crop disease management, mainly focusing on tropical fruits. Studies reviewed suggest that essential oils and plant extracts can be effective at preventing fungal and bacterial infections, as well as controlling crop disease progression at the pre and postharvest stages of the tropical fruit supply chain. Positive results from edible coatings and as juice preservatives formulated with essential oils and plant extracts also point towards the potential for commercial use in the industry as more chemically safe and environmentally friendly biopesticides.